(3caGjI GdeJcde aj BOGH GdYGde hGdeJYdes - (3HOQ GdOjf eMeO Hf EHQGgje Hf SYO Gddg Hf LeGYI GdcfGfj,J (B740 (3g` s ((3eMeO Hf Ydi Hf YHO Gddg Hf eMeO GdeZQHi s)
(3ChdgG (B:s
(3GdMeO ddg GdHQ GdQMje GdhGSY GdYdje CeG HYO aEf ef Cge eG jHGOQ Hg GddHjH hGcJSGHg MSf GdGOH s
(3BNQgG (B:s
(3hdG jJcde MJi jfXQ aGFOI dbhdg Udi Gddg Ydjg hSde (B( (3ef JQc GdeQGO hgh eMb Hfi dg HjJ ai CYdjI GdLfI (B) (3aEf Pdc GbWY GdGfJTGQ GdZVH Ke cJGH GdBOGH hGdMeO ddg QH GdYGdejf s
(3GdMHQ HGgJ LOkGs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI SjFI s
(3GdfSNI HgG JdhjK , CQVg s
Keywords: (3GdeYGQa GdYGeIs